2023
DOI: 10.1007/s12672-023-00672-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and circular RNAs: promising partners in hepatocellular carcinoma from bench to bedside

Abstract: Hepatocellular carcinoma (HCC) is characterized by high morbidity and mortality, and a low 5-year survival rate. Exploring the potential molecular mechanisms, finding diagnostic biomarkers with high sensitivity and specificity, and determining new therapeutic targets for HCC are urgently needed. Circular RNAs (circRNAs) have been found to play a key role in the occurrence and development of HCC, while exosomes play an important role in intercellular communication; thus, the combination of circRNAs and exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Furthermore, when circRNA is enclosed within exosomes, its stability is further enhanced [ 86 ]. With its stability and function of regulating miRNA splicing, exosomal circRNAs play a crucial role in the progression, immune escape, invasion, and drug resistance of HCC [ 87 , 88 , 89 ]. Recent studies have also shown that exosome circRNAs possess the ability to be novel biomarkers for the diagnosis and forecasting of HCC.…”
Section: Exosome Cargos As Biomarkers For Hccmentioning
confidence: 99%
“…Furthermore, when circRNA is enclosed within exosomes, its stability is further enhanced [ 86 ]. With its stability and function of regulating miRNA splicing, exosomal circRNAs play a crucial role in the progression, immune escape, invasion, and drug resistance of HCC [ 87 , 88 , 89 ]. Recent studies have also shown that exosome circRNAs possess the ability to be novel biomarkers for the diagnosis and forecasting of HCC.…”
Section: Exosome Cargos As Biomarkers For Hccmentioning
confidence: 99%
“…The unique advantages of exosomes and circular RNAs have demonstrated the promise of exosomal circRNAs, as important markers for the prognosis of HCC, in the regulation and control of the malignant biological behavior of HCC 12,25 . However, the prognostic nomogram models of HCC still require more scienti c and reliable methods, especially prognostic nomograms containing genes 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA is a circular molecule with a high degree of stability and conservation; thus, abnormal expression of these molecules plays an essential role in the proliferation, metastasis, invasion and drug resistance of liver cancer [9][10][11] . Notably, several recent studies have offered a more in-depth understanding of the use of exosome-enriched circRNA expression pro les in HCC as they relate to tumorigenesis, metastasis, angiogenesis, and immunomodulation and the diagnosis and treatment of HCC 12 . For example, Hu et al explored exosomal circRNA expression pro les and con rmed that exosomal circCCAR1 facilitates the growth and metastasis of HCC, diminishing the treatment e cacy and patient life span 13 .…”
Section: Introductionmentioning
confidence: 99%
“…circRNA has a closed circular structure, which is more stable and not easily degradable by exonuclease [132]. Moreover, being carried inside exosomes renders them difficult to be degraded by enzymes [133]. In the last few years, the role of circRNAs has been investigated; they play a vital role in biological functions, they are certainly known to function as competing endogenous RNA (ceRNA), and, together with miRNAs, they regulate the stability of target RNAs and gene expression [134,135].…”
Section: Circrna-extracellular Vesiclesmentioning
confidence: 99%